PENYULUHAN KENAKALAN REMAJA PADA SISWA SMP NEGERI 01 TIRTOYUDO KEC. TIRTOYUDO KAB. MALANG SEBAGAI BENTUK KEPEDULIAN TERHADAP MASA DEPAN GENERASI BANGSA - Yani Sulis Tyoningsih; Farizha Irmawati; Nur Khozanah Ilmah (JPM PAMBUDI, 2023)
This community service activity regarding counseling on juvenile delinquency for students of SMP Negeri 01 Tirtoyudo, Tirtoyudo District, Malang Regency aims to fix the dilapidated lifestyle of junior high school students who are in their teens and what negative effects they get when they choose to be outside the scope of his teenage years. They can experience negative effects if outside their scope, among other things. abuse of narcotics, sex outside of marriage, promiscuity, rape, bullying and even brawls. The method used in this community service activity is direct counseling in collaboration with several agencies such as the Gadungsari village hall, the SMP N 1 Tirtoyudo school and the Tirtoyudo sub-district Community Health Center The material presented in this counseling activity is various kinds of juvenile delinquency, the bad effects that will be felt when entering into juvenile delinquency and how to overcome so as not to fall into this behavior. The output of this counseling activity is that students at SMP Negeri 1 Tirtoyudo are equipped to be able to respond to the impact of the progress of the globalization era, one of which is having a bad impact on those who are unable to sort out the good things. They are expected to be able to realize these provisions in themselves so that they become superior quality next generations.